2023
DOI: 10.21014/actaimeko.v12i3.1445
|View full text |Cite
|
Sign up to set email alerts
|

A procedure for the characterization of a music instrument vibro-acoustic fingerprint: the case of a contemporary violin

Marco Casazza,
Fabrizio Barone,
Elvio Bonisoli
et al.

Abstract: Violins are wooden musical instruments, whose quality is mainly evaluated on the basis of their aesthetics, as well as depending on the historical relevance of their makers. However, their acoustic quality remains a key evaluation parameter for performers and listeners. The instrument perceived quality, in turn, depends on one side, on the player, the environmental conditions and on the listeners’ psychoacoustic factors. On the other side, the quality of a violin depends on its materials, constructive and set-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Casazza et al [6] investigate a procedure for the vibroacoustic characterization of violins, named vibro-acoustic fingerprint, as an example of characterisation of a wooden musical instrument. The procedure was applied, as a case study, to an Italian contemporary violin and showed to be useful in detecting the influence of instrument ageing on its vibro-acoustic properties, as well as a support to the restoration of historical instruments.…”
mentioning
confidence: 99%
“…Casazza et al [6] investigate a procedure for the vibroacoustic characterization of violins, named vibro-acoustic fingerprint, as an example of characterisation of a wooden musical instrument. The procedure was applied, as a case study, to an Italian contemporary violin and showed to be useful in detecting the influence of instrument ageing on its vibro-acoustic properties, as well as a support to the restoration of historical instruments.…”
mentioning
confidence: 99%